Non-traditional lipid parameters are independent predictors of the location, distribution, and stroke events of moderate-to-severe intracranial and extracranial atherosclerotic stenosis - Yin Fei Huang; Zhen Xing Liu; Kuan Cen; Ren Wei Zhang; Qiao Yuan Xiang; Qi Cai; Chun Jiao Yang; Lei Luo; Hai Long Xu; Yu Xie; Yu Min Liu (Frontiers in Neurology)
ObjectiveModerate-to-severe stenosis has been identified as a significant risk factor for stroke recently. This study aims to investigate the relationship between non-traditional lipid parameters and the location and distribution of stenosis, as well as symptomatic events, in patients with moderate-to-severe intracranial atherosclerotic stenosis (ICAS) and extracranial atherosclerotic stenosis (ECAS).MethodsThis study analyzed correlation between non-traditional lipid parameters and moderate-to-severe ICAS and ECAS concerning stenosis location, distribution, and the presence or absence of symptoms. Logistic models and restricted spline analysis were utilized to explore the relationship between Castelli's risk index-II (CRI-II) and the occurrence of stroke events.ResultsThe present study comprised 1,030 participants, of whom 143 were non-stenotic and 887 were patients with moderate-to-severe stenosis. The study focuses on the latter and indicated statistically significant differences in AIP, LCI, RC, AC, CRI-I, and CRI-II among the three groups of ICAS, ECAS, and combined ICAS and ECAS (P = 0.012, 0.005, 0.013, 0.009, 0.009, 0.032, respectively). Lipid parameters for ICAS were generally higher than those for ECAS. Remnant cholesterol (RC) exhibited a discrepancy among the anterior, posterior, and combined anterior and posterior circulation stenosis groups (P = 0.047). Logistic regression analysis revealed that CRI-II (Odds ratio [OR] = 1.20, Confidence interval [CI] 1.03–1.40, P = 0.009) and low-density lipoprotein cholesterol (LDL-c) (OR = 1.21, CI 1.03–1.42, P = 0.011) demonstrated remarkable elevations in symptomatic stenosis patients compared to patients without symptoms. After adjusting for potential confounding factors, CRI-II remained an independent risk factor for symptomatic stenosis. Furthermore, multivariate spline regression modeling elucidated that an augmented risk of stroke events in moderate-to-severe stenosis was associated with an elevated CRI-II. As CRI-II elevated, the risk of stroke events increased progressively.